EVALUATION OF THE EXPERT PATIENT PANLAR SELF-MANAGEMENT PROGRAM IN RHEUMATOID ARTHRITIS. A PILOT STUDY IN ARGENTINA, COLOMBIA AND PANAMÁ - Emilia Arrighi; Ana Paula León; Carlo V caballero-Uribe (Global Rheumatology)
Introduction: Education is a cornerstone of the comprehensive management of patients living with rheumatic and musculoskeletal diseases (RMSDs). It allows them to optimize their self-care for health maintenance.